The Life Philosophical Background of The Characters in the Novel Canting By Arswendo Atmowiloto and Fissilmi Hamida: (An Intertextual Study) - Elok Harisma Kartikasari; Suyitno Suyitno; Andayani Andayani (Jurnal Linguistik Terapan, 2020)
This research discusses the intertextual study of the novel Canting written by Arswendo Atmowiloto and another novel with the same title by Fissilmi Hamida. The basis for the intertext study is the life philosophical background differences and similarities possessed by the characters in the two novels. This research is descriptive qualitative research, and the object of research are all quotations related to the philosophical background of the characters in the novels. Data collection is carried out with content analysis. Data analysis techniques in this study were carried out in the following steps, (1) data collection, (2) data reduction, (3) data presentation, and (4) drawing conclusions. The results of the analysis show that there is a slight relationship between the novel by Arswendo Atmowiloto (as the hypogram) and the novel Canting by Fissilmi Hamida (as the transformation) when viewed from the life philosophical background of the characters. In this case, the philosophical background of the characters is based on the main foundations of the Javanese philosophy of life, namely (1) divinity conscious awareness and (2) conscious awareness of human existence which emphasizes human relationships with others. Thus, intertextually the novel by Fissilmi Hamida is a deviant transformation of its hypogram, the novel by Arswendo Atmowiloto.